Δημόσιο έλλειμμα, δημόσιο χρέος και η φερεγγυότητα του ελληνικού δημόσιου τομέα - Αργείτης Γεώργιος (SPOUDAI Journal of Economics and Business, 2000)
This paper uses the Hamilton-Flavin test of public sector solvency and applies it in the Greek economy. Under the maintained hypothesis that the government solvency constraint needs to be imposed, this test develops from the idea of verifying whether the intertemporal budget constraint of the public sector would be satisfied (a) if the fiscal policy in the sample had been pursued indefinitely and (b) if the relevant macro and structural features of the economy were stable over time. If solvency is not supported by the empirical evidence, a change either in the implemented fiscal policy or in the relevant macro and structural variables (growth rate, inflation rate, interest rate, etc.) must occur. The empirical work conducted in this paper provides evidence that public sector solvency seems to be a problem in the Greek economy since the end of the last decade, questioning the sustainability of fiscal policies applied in the past. JEL Classification: E62, H30